InfoLibre and eldiario.es, the appearance of two digital newspapers advocates of a more democratic and participatory journalism - Rubio Jordán, Ana Virginia (Historia y Comunicación Social, 2014)
InfoLibre and eldiario.es are two emerging media that due to the crisis in jourmalism, are born only in digital format. These diaries are presented as defenders of the major democratic ideals, freedom of the press and human rights, among other. Its formula mixed funding allows them to obtain income in two ways: through the contributions made by its members and by selling advertising space.